Peripheral markers of neurochemical function among workers exposed to styrene. Issue 8 (August 1992) - Checkoway, H; Costa, L G; Camp, J; Coccini, T; Daniell, W E; Dills, R L
Abstract : A cross sectional study of biological markers of neurochemical function in peripheral blood cells, and self reported nervous system symptoms, was conducted among 60 workers exposed to styrene in three reinforced plastics plants and 18 reference workers not exposed to styrene or other solvents. Concentrations of styrene in the air at the plants ranged from less than 1 to 160 ppm. Biomarkers of neurochemical function measured were: sigma receptor binding in lymphocytes, monoamine oxidase type B (MAO-B) activity in platelets, and serotonin uptake by platelets. Blood styrene concentration was used as the exposure index to take account of the use of protective equipment and dermal uptake. Four blood styrene exposure groups were defined as: non-exposed (reference) and exposed to less than 0.05, 0.05-0.19, and greater than or equal to 0.20 micrograms/ml. The prevalences of headache, dizziness, light headedness, fatigue, irritability, memory loss, and feeling "drunk" at work increased with increasing blood styrene concentration. No effect on sigma receptor binding was seen. A slight positive correlation was found for uptake of serotonin, which has been used as an exposure related effect indicator in previous studies of workers exposed to solvents. The MAO-B activity decreased with increasing blood styrene concentration; the mean (SE) MAO-B values for the four groups were 34.2 (3.0), 28.1 (5.3), 20.1 (4.8), and 16.9 (7.7) pmol/10(7) cells/min. The MAO-B activity also correlated negatively with the number of reported nervous system symptoms, whereas no associations were seen between prevalence of symptoms and either serotonin uptake or sigma receptor binding. The findings for MAO-B activity are consistent with previously reported experimental data, and suggest that MAO-B may be a useful marker of styrene neurotoxicity.